Application of a multi-disciplinary approach to reveal population structure and Southern Ocean feeding grounds of humpback whales. (June 2018) - Riekkola, Leena; Zerbini, Alexandre N.; Andrews, Olive; Andrews-Goff, Virginia; Baker, C. Scott; Chandler, David; Childerhouse, Simon; Clapham, Phillip; Dodémont, Remi; Donnelly, David; Friedlaender, Ari; Gallego, Ramon; et al.
Highlights: Humpback whales tracked from breeding to unknown Antarctic feeding grounds. Feeding grounds span 4500 km, revealing vast ecological range. Different reproductive state may affect feeding ground choice. Multi-disciplinary approach valuable when studying 'hard to reach' animals. Recovering whales are important ecological indicators in the Southern Ocean. Abstract: Obtaining direct measurements to characterise ecosystem function can be hindered by remote or inaccessible regions. Next-generation satellite tags that inform increasingly sophisticated movement models, and the miniaturisation of animal-borne loggers, have enabled the use of animals as tools to collect habitat data in remote environments, such as the Southern Ocean. Research on the distribution, habitat use and recovery of Oceania's humpback whales ( Megaptera novaeangliae ) has been constrained by the inaccessibility to their Antarctic feeding grounds and the limitations of technology. In this multi-disciplinary study, we combine innovative analytical tools to comprehensively assess the distribution and population structure of this marine predator throughout their entire migratory range. We used genotype and photo-identification matches and conducted a genetic mixed-stock analysis to identify the breeding ground origins of humpback whales migrating past the Kermadec Islands, New Zealand. Satellite tracking data and a state-space model were then used to identify the migratory paths and behaviour of 18 whales, and to reveal their Antarctic feeding ground destinations. Additionally, we conducted progesterone assays and epigenetic aging to determine the pregnancy rate and age-profile of the population. Humpback whales passing the Kermadec Islands did not assign to a single breeding ground origin, but instead came from a range of breeding grounds spanning ∼3500 km of ocean. Sampled whales ranged from calves to adults of up to 67 years of age, and a pregnancy rate of 57% was estimated from 30 adult females. The whales migrated to the Southern Ocean (straight-line distances of up to 7000 km) and spanned ∼4500 km across their Antarctic feeding grounds. All fully tracked females with a dependent calf (n = 4) migrated to the Ross Sea region, while 70% of adults without calves (n = 7) travelled further east to the Amundsen and Bellingshausen Seas region. By combining multiple research and analytical tools we obtained a comprehensive understanding of this wide-ranging, remote population of whales. Our results indicate a population recovering from exploitation, and their feeding ground distribution serves as an indicator of the resources available in these environments. The unexpected Kermadec Islands migratory bottle-neck of whales from several breeding grounds, variable distribution patterns by life history stage and high pregnancy rates will be important in informing conservation and management planning, and for understanding how this, as well as other whale populations, might respond to emerging threats such as climate change.